Evidence for Cognitive Impairment in Mastocytosis: Prevalence, Features and Correlations to Depression - Moura, Daniela Silva; Sultan, Serge; Georgin-Lavialle, Sophie; Barete, Stéphane; Lortholary, Olivier; Gaillard, Raphael; Hermine, Olivier (PLOS ONE, 2012)
Mastocytosis is a heterogeneous disease characterized by mast cells accumulation in one or more organs. We have reported that depression is frequent in mastocytosis, but although it was already described, little is known about the prevalence and features of cognitive impairment. Our objective was to describe the prevalence and features of cognitive impairment in a large cohort of patients with this rare disease (n = 57; mean age = 45) and to explore the relations between memory impairment and depression. Objective memory impairment was evaluated using the 3rd edition of the Clinical Memory scale of Wechsler. Depression symptoms were evaluated using the Hamilton Depression Rating Scale. Age and education levels were controlled for all patients. Patients with mastocytosis presented high levels of cognitive impairment (memory and/or attention) (n = 22; 38.6%). Cognitive impairment was moderate in 59% of the cases, concerned immediate auditory (41%) and working memory (73%) and was not associated to depression (p≥0.717). In conclusion, immediate auditory memory and attention impairment in mastocytosis are frequent, even in young individuals, and are not consecutive to depression. In mastocytosis, cognitive complaints call for complex neuropsychological assessment. Mild-moderate cognitive impairment and depression constitute two specific but somewhat independent syndromes in mastocytosis. These results suggest differential effects of mast-cell activity in the brain, on systems involved in emotionality and in cognition.